"If You Build It, Will They Come?" Piloting a Multi-Day Collaborative Research Workshop within a Learning Management System. Issue 3 (1st October 2016) - Chin Roemer, Robin; Greer, Rebecca
ABSTRACT: Research workshops are designed to help students develop skills that go beyond the scope of one-shot library sessions. However, with more students conducting research off-campus, online, and in the evening, workshops targeted towards complex skills and competencies are difficult to offer. But what if librarians were to design and deliver intensive workshops online? By removing the constraints of time and space, librarians can bring active learning and collaboration to an environment that meets student demand. This paper describes one research library's experience with the development, implementation, and assessment of a multi-day, asynchronous, online workshop, targeted at teaching "Effective Literature Review."